2000
DOI: 10.1016/s0022-5223(00)70016-x
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-induced apoptosis in non–small cell lung cancer cell lines is associated with increased caspase-3 activity

Abstract: Paclitaxel induces apoptosis in lung cancer cell lines, as assessed by a consistent increase in caspase-3 activity, DNA laddering, and characteristic morphologic changes. Paclitaxel-induced apoptosis in human lung cancer cells is associated with caspase-3 activation but is not Fas dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…These results indicate that it may be possible to reduce the side effects of PTX whilst enhancing its clinical efficacy by using it in combination with CZEO. PTX can arrest the cell cycle at the G 2 /M phase and induce caspase-3 enzymatic activity (29)(30)(31)(32). In the present study, treatment with the combination of CZEO and PTX increased the accumulation of cells in the G 2 /M phase, and the expression levels of caspase-3.…”
Section: Discussionsupporting
confidence: 58%
“…These results indicate that it may be possible to reduce the side effects of PTX whilst enhancing its clinical efficacy by using it in combination with CZEO. PTX can arrest the cell cycle at the G 2 /M phase and induce caspase-3 enzymatic activity (29)(30)(31)(32). In the present study, treatment with the combination of CZEO and PTX increased the accumulation of cells in the G 2 /M phase, and the expression levels of caspase-3.…”
Section: Discussionsupporting
confidence: 58%
“…Activation of caspase-3 was also observed during taxol-induced apoptosis in other cell lines including human acute myelocytic leukemia HL-60 cells, 23,27 human lung cancer cell lines 24 and human gastric cell lines. 28,29 These and other results support the notion that different apoptotic pathways may be used by the same apoptotic stimulus in various cells.…”
Section: Caspase-9 Is Not Processed In Taxol-treated Skov3 and Mcf7 Cmentioning
confidence: 81%
“…22 The fact that several apoptotic pathways coexist in mammalian cells suggests that it is important to reveal the mechanism of apoptosis induced by drugs in cancer therapy. Recent studies demonstrated that HL-60 leukemia cell lines 23 and non-small cell lung cancer cell lines 24 are susceptible to taxol-induced apoptosis and that caspase-3 is activated by taxol in these cells. Since breast and ovarian cancer are the main targets of taxol chemotherapy, we decided to study the mechanism of caspase activation following taxol treatment of these types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 However, data from MCF-7 cells and analysis of caspase-3 knockout mice have shown that caspase-3 deficiency cannot block the caspase cascade. 34 Identification of specific activators of different caspases could be useful for caspase-based gene therapy of cancer.…”
Section: Discussionmentioning
confidence: 99%